Recycling stories: Lessons from community arts-based process and exhibition in Brazil. Issue 2 (November 2016) - de Oliveira Jayme, Bruno; Monk, David; Tremblay, Crystal
How can we create meaningful adult education and engagement opportunities for people who work in the recycling industry in Brazil and suffer marginalisation? This question guided the development of a series of community arts-based workshops and public exhibits in São Paulo. In this article, we share the stories of two workers from the recycling industry (i.e. recyclers), and describe how they experienced the potential of art-making and public exhibits. We worked in collaboration with an environmental adult education organisation that aims to expose the recyclers' realities of poverty, their difficult working conditions and their fight for greater visibility and social inclusion. The stories show how community created art exhibits constructed important visual meaning-making openings, attracted broad public attention and even provided income generation for those involved in the recycling industry.